2020
DOI: 10.1186/s12935-020-01511-5
|View full text |Cite
|
Sign up to set email alerts
|

Promoter methylation, transcription, and retrotransposition of LINE-1 in colorectal adenomas and adenocarcinomas

Abstract: Background: The methylation of the CpG islands of the LINE-1 promoter is a tight control mechanism on the function of mobile elements. However, simultaneous quantification of promoter methylation and transcription of LINE-1 has not been performed in progressive stages of colorectal cancer. In addition, the insertion of mobile elements in the genome of advanced adenoma stage, a precancerous stage before colorectal carcinoma has not been emphasized. In this study, we quantify promoter methylation and transcripts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 77 publications
3
11
0
Order By: Relevance
“…Global DNA hypomethylation, measured by LINE-1, was previously recognized as a molecular feature able to confer a higher predisposition to the development of colorectal adenomas and cancers [ 9 , 20 ]. Jiang and colleagues reported that LINE-1 hypomethylation increased in the transition from normal mucosa to CRC and could be used to predict the onset of synchronous CRCs [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Global DNA hypomethylation, measured by LINE-1, was previously recognized as a molecular feature able to confer a higher predisposition to the development of colorectal adenomas and cancers [ 9 , 20 ]. Jiang and colleagues reported that LINE-1 hypomethylation increased in the transition from normal mucosa to CRC and could be used to predict the onset of synchronous CRCs [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the specific role of LINE-1 methylation in the transition from normal mucosa to adenoma was proved by a genome-wide expression analysis based on the comparison of normal adjacent, adenomatous and CRC tissues [ 17 ]. Overall, the number of studies testing the involvement of epigenetic regulatory mechanisms in colorectal adenoma–carcinoma transition is rapidly growing [ 20 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the assessment of methylated LINE-1 may serve as a valuable tool for cancer screening. Two studies also evaluated hypomethylation of long interspersed nuclear element-1 (LINE-1) as a potent early detection biomarker in CRC [ 76 , 77 ]. Measurement of cell-free DNA long interspersed nuclear element-1 hypomethylation index (cfDNA LHI) was achieved with 63.2% sensitivity and 90% specificity for early-stage I/II CRC [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…The assessment of LINE-1 transcripts with qRT-PCR is technically feasible for the screening of a large number of samples as used previously [26,42] but is probably biased by the fact that LINE-1 sequences are incorporated in intronic regions of various genes and can undergo "pass through" transcription not related to the L1 promoter. The precise evaluation of the expression of repetitive elements is very challenging and requires sophisticated methods based on whole transcriptome analysis [43].…”
Section: Discussionmentioning
confidence: 99%